Review on Lateral Stability of Piled Riverine Structures in the Estuaries of Sarawak - Lin Jye, Lee; R. Kaniraj, Shenbaga; Noor Linda bt Taib, Siti; bin Sahdi, Fauzan (International Journal of Engineering and Technology, 2018)
Soft soil conditions with very soft and deep silty clay have constantly endangered the stability of the riverine and estuarine structures in Sarawak. There have been many failures of jetties, wharves and bridges in Sarawak. In many cases of failures, the piles were not designed to resist the lateral movement, unless they were included to stabilize unstable slopes or potential landslides. This practice may be due to reasons such as erroneously judging the river bank as stable in slope stability analysis or simply due to the inexperience of designers. Also, when the river bank approaches the limiting stability in its natural state any construction activity on the river bank could result in lateral soil movement. This paper highlights this important geotechnical problem in Sarawak. Then it presents the details of a few failures of estuarine structures. A review of situations causing lateral loading of piles is then presented. The results of the in-soil and in-pile displacement measurements are shown in this paper and it is found that the computation made to compare between field and 3D modeling is agreeable.
Keywords: Bridges; Foundation; Lateral stability; Modelling; Soft soils.